Study on DSP and PSP toxic profile in Haliotis tuberculata - Gago Martínez, A.; Comesaña Losada, M.; Leao Martins, J. M.; Rodríguez Vázquez, J. A. (Ciencia, 1970)
Galician coastal waters (NW of Spain) present the suitable conditions for the growth of a great amount of different species, overail the bivalve molluscs. However, the presence of marine biotolens during some periods of the year seriously affects the Galician industry, causing important socioeconornic damage. The abalone, Haliotis tuberculata, is a species that it was began to exploit since time ago. This species is exported to Japan where it is very appreciated. The abalones are also affected by the appearance of severai species of dinoflagellatesi marine phytoplankton which produce paralyhc (PSP) and diarrhetic toxins (DSP). Bioassay with mouse is the officiai method for the analysis of these toxic compounds but due to its lack of sensiüvity. High Performance Liquid Chromatography with fluorescent detection (HPLC-FLD) was proposed as a n anaiyticai aitemative because of its sensibility and selectivity for these toxic components. In this study we report on the work carried out by applying HPLC-FLD methods for the anaiysis of marine biotoxins present on the studied samples.